A bidimensional reformulation of location quotients for generating input–output tables. Issue 4 (1st October 2020) - Pereira-López, Xesús; Carrascal-Incera, André; Fernández-Fernández, Melchor
ABSTRACT: The difficulties in obtaining input–output tables at subnational levels have led to multiple methodological developments in order to obtain local technical coefficients using semi-survey approaches. A widely accepted method is based on the use of location quotients (LQ) according to Flegg's formula (AFLQ). However, it makes the adjustment of purchasing sectors proportionally to the productive specialization, which has significant implications for the estimation of domestic coefficients. In this paper, an alternative formulation is presented as a generalization of Flegg's methodology, characterized by using a bidimensional approach that provides better results, as shown in the empirical application implemented.